Sovereign credit rating bias: a comparative analysis of developed and developing countries - Jeyi, Siviwe (My University, 2021)
Through the use of an ordered response framework and panel data, this study examines sovereign credit rating bias in Fitch, Moody’s, and S&P’s ratings assignments. The data sample comprises 118 countries from 1996 to 2019. First, the full sample is estimated; the data sample is then divided according to development levels and estimated separately to determine variations between developed and developing countries. The results provide evidence that developed countries are rated higher despite the performance of economic fundamentals and developing countries are rated according to the theorised relationship between macroeconomic fundamentals and sovereign credit ratings. Moreover, this paper also finds that institutional quality is the source of the bias toward developed countries and against developing countries
A research report submitted in partial fulfilment of the degree of Master of Commerce (Economics) in the School of Economics and Finance, University of the Witwatersrand, 2021